Radiometric Ages of Granitic Rocks, Cape Breton Island, Nova Scotia - Cormier, Randall F. (Canadian Journal of Earth Sciences, 1972)
Rubidium–strontium whole-rock and mineral ages of granitic rocks from fourteen localities on Cape Breton Island have been measured. The ages cluster about a mean value of about 560 m.y. and indicate that most of the granitic rocks on the island have primary ages that are close to the Cambrian–Precambrian (Hadrynian) boundary. Some of the granitic rocks, particularly in the northern highlands, may have considerably younger, Siluro–Devonian (Acadian?), primary ages. Evidence is presented suggesting that simple biotite ages are not always reliable for the measurement of primary ages of granitic rocks. It. is suggested that, the granitic rocks having primary ages close to the Cambrian-Precambrian boundary be referred to a hitherto generally unrecognized episode of granitic intrusion, the Bretonian.